The Effect of a Values-Based Problem-Based Learning (PBL) Model, Drawing on the Novel Keep Being Stupid, Don’t Be Smart, on Improving Science Literacy and Environmental Awareness Among Year 10 Students at MA Al-Amiriyyah - Isytaqul Alfa Utomo; Risma Nurlim (The Eastasouth Journal of Learning and Educations, 2026)
Students’ science literacy levels, as measured by PISA scores, are classified as low. Students’ lack of skills, the low application of scientific knowledge in daily life, and the slow decision-making process are caused by low science literacy and a lack of environmental awareness. One approach to improving science literacy and environmental awareness is the use of a values-based problem-based learning model, as illustrated in the novel Teruslah Bodoh Jangan Pintar, to be implemented. This study aims to: 1) Determine the significant effect of using a values-based problem-based learning model, as illustrated in the novel Teruslah Bodoh Jangan Pintar, on improving the science literacy of Year 10 students at MA AL-Amiriyyah. 2) To determine the significant effect of using a problem-based learning model supported by values from the novel Teruslah Bodoh Jangan Pintar on improving the environmental awareness of Year 10 students at MA AL-Amiriyyah. This study employed a quantitative approach using a quasi-experimental design, specifically a non-equivalent control group design. The study population comprised Year 10 students at MA AL-Amiriyyah, Banyuwangi, with a purposive sampling technique used to select Class X F as the experimental group and Class X H as the control group. Data collection techniques included questionnaires, tests, and documentation. Data analysis employed the Z-test. The results indicate that there is a significant effect of using a values-based problem-based learning model, informed by the novel Teruslah Bodoh Jangan Pintar, on improving science literacy and environmental awareness among Year 10 students at MA AL-Amiriyyah. Based on the results of the Mann-Whitney U test, Sig (2-tailed) = 0.000 < 0.05, with a strong category for science literacy, and based on the results of the Z-test, Sig (2-tailed) = 0.001 < 0.05, with a weak category for environmental awareness. Based on the data analysis, it can be concluded that science literacy skills and environmental awareness attitudes improved through the problem-based learning model supported by the values in the novel Teruslah Bodoh Jangan Pintar.